Systemic Thinking And Its Relation To The Episodic Buffer Of University Students - Ali Ehsan, Afak Basim (Opción, 2019)
The current research aims to identify: 1- Knowing the level of Systemic think- ing among university students. 2- Knowing the level of transverse buffer for university students. 3- Knowing the relationship between coordinating think- ing and the occasional condom of university students. 4- Knowing the dif- ferences in the relationship between Systemic thinking and the occasional condom of university students according to the gender variable. 5- Knowing the differences in the relationship between coordinating thinking and the oc- casional dielectric of university students according to the variable of special- ization.